NK Cell-Based Immunotherapy and Therapeutic Perspective in Gliomas - Pan, Changqing; Zhai, You; Li, Guanzhang; Jiang, Tao; Zhang, Wei (Frontiers in Oncology, 2021)
The cancer immunotherapy field has rapidly grown in the past few years, largely driven by the success of immune checkpoint blockade. However, the immunotherapies for solid tumors represented by glioma have not achieved the ideal therapeutic effect. Compared to T cell-based immunotherapy, natural killer (NK) cells are an intriguing candidate for the next wave of therapies because of several unique features that they possess. For example, NK cell-based immunotherapy causes minimal graft-versus-host disease. Cytokine release syndrome is less likely to occur during chimeric antigen receptor (CAR)-NK therapy, and CAR-NK cells can kill targets in a CAR-independent manner. The efficacy of NK cell-based cancer immunotherapy depends on the presence of sufficient highly cytotoxic NK cells. However, NK cells are not typically clonally expanded, and thus, the expansion of NK cells is challenging. In addition, CAR molecules are not sufficiently well designed so that they will thoroughly release functioning NK cells. Here, we review several unique features of NK cells and propose several strategies that will improve the efficacy of CAR-NK cells in the treatment of glioma.